1981
DOI: 10.1128/jcm.14.5.550-556.1981
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of material colonization with group B streptococci by use of fluorescent antibody

Abstract: To identify women colonized with group B streptococci during parturition, we used pooled type-specific fluorescent antibody to examine vaginal swabs enriched by preincubation in selective broth medium. In preliminary experiments, group B streptococcus strain III-Bell was reliably detectable with fluorescent antibody at concentrations of greater than 10(5) colony-forming units per ml, achieved after 6 h of incubation of small inocula (18 to 26 colony-forming units). Of the vaginal swabs from 924 parturient wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A sensitivity analysis excluding studies with known or possible antibiotic use showed a slight increase in prevalence of neonatal infections in studies that tested lab outcomes (1.1%, 95% CI 0.2-2.0), studies that diagnosed clinical signs of neonatal infection (6.5%, 95% CI -6.5-19.5), and studies that collected clinical signs of infection and conducted labs tests (7.6%, 95% CI 1.4-13.8).
Figure 3 Maternal colonization and neonatal infection [ 54 - 86 ] .
…”
Section: Resultsmentioning
confidence: 99%
“…A sensitivity analysis excluding studies with known or possible antibiotic use showed a slight increase in prevalence of neonatal infections in studies that tested lab outcomes (1.1%, 95% CI 0.2-2.0), studies that diagnosed clinical signs of neonatal infection (6.5%, 95% CI -6.5-19.5), and studies that collected clinical signs of infection and conducted labs tests (7.6%, 95% CI 1.4-13.8).
Figure 3 Maternal colonization and neonatal infection [ 54 - 86 ] .
…”
Section: Resultsmentioning
confidence: 99%
“…If the mother is colonized with GBS, the bacteria can pass from the vagina into the amniotic fluid and cause IUFD and preterm birth (130,131). A further risk for exposure happens during passage through the birth canal (132) and after birth via breast milk or the environment (133,134).…”
Section: Neonates and Infantsmentioning
confidence: 99%
“…When traditional techniques for the detection of streptococci are used, at least 18 h elapse between the receipt of a specimen and the issuance of a culture report; however, there are some circumstances such as major burns for which the early detection of Streptococcus pyogenes may be important. Various methods for the earlier detection of S. pyogenes and other streptococci have been described, including short incubation of swabs in selective enrichment broths followed by fluorescent-antibody staining (1,9), staphylococcal coagglutination (10,11), latex agglutination (7,9), or counterimmunoelectrophoresis (4) to detect streptococcal antigens in the broth. Methods involving the direct examination of the specimen include the use of fluorescentantibody staining smears (6, 8), the extraction of throat scrapings with nitrous acid and precipitation detection of antigen (5), and the detection of streptococcal antigen in throat gargles with latex agglutination (3).…”
mentioning
confidence: 99%
“…The Streptex method has been shown to be reliable for TABLE_ 1 a Values in parentheses are the percentages of total positive isolations. The average percentages were: 81% (isolation and latex agglutination), 19% (isolation), and 6% (latex agglutination).…”
mentioning
confidence: 99%